Development of Edutainment Learning Media History Adventure Indonesian Hindu-Buddhist History Based on Local History Bima-Dompu - Husnul Khatimah; Hasan; Indah Afrianti (Universitas Hamzanwadi, 2024)
Historian Adventure is an edutainment learning medium that incorporates both educational and entertainment components with the objective of rendering the process of learning history more engaging and interactive. The objective of this research is to develop edutainment learning media, Historian Adventure, on Indonesian history during the Hindu-Buddhist period based on Bima-Dompu local history at the university level. The research methodology employed is that of development research (R&D), with reference to Thiagarajan's 4-D (Four-D) model, which comprises four stages: defining, designing, developing, and disseminating. This research involved the input of material experts, learning media experts, and 30 students enrolled in the History Education Study Program at STKIP Yapis Dompu. The results of the feasibility study indicate that the developed media meets the highest standards of feasibility, with an initial assessment by media experts yielding a score of 89.23% (very feasible) and an increased score of 95.38% in the second stage. The results of the initial trial demonstrated a feasibility score of 86.54%, indicating a high level of suitability for the intended purpose. The subsequent trial yielded a similar score of 86.64%, confirming the continued high feasibility of the learning media. In light of the aforementioned results, it can be posited that the Historian Adventure learning media is an efficacious pedagogical tool for the acquisition of knowledge pertaining to Indonesian history during the Hindu-Buddhist period, based on local history. The adventure format enables students to engage with historical events, identify Hindu-Buddhist kingdoms, and comprehend the impact of Hindu-Buddhist religion and culture, particularly in the context of Bima-Dompu.